With one white wing : puzzles in poems and pictures - Spires, Elizabeth; Blegvad, Erik (New York : M.K. McElderry Books, 1995)
A collection of twenty-six puzzles, illustrated in full color, with verbal and pictorial hints, ranging in answer from a bumblebee to a swimming pool.
Wilson's Children.
School Library Journal starred.
Booklist.
2.1
K-3
Keywords: Children's poetry; Puzzles -- Juvenile literature; Riddles, Juvenile; American poetry; Picture puzzles; Riddles; Children's poetry; Puzzles; Riddles; Puzzles; Riddles; Picture puzzles; American poetry